Novel use of XRF in the adsorption processes for the direct analysis of cadmium and silver in absorbent Na-alginate beads (Baghdad Science Journal, 2020)
The Na-alginate bead is commonly used in biotechnology fields such as adsorption due to ion exchange between Ca and Na with elements. Scanning electron microscopy (SEM-EDX) has proven to be a comparative method in the detections of these adsorbed elements, but the un-flat forming area of beads that can introduce impossible of the detection of element adsorbed. In contrast, X-ray fluorescence (XRF) documents analysis of elements, direct examination, which may analysis the adsorbents of elements. Here, this Study evaluated the possibility by using XRF for the direct analysis for examples of Cd and Ag in a bench stand. This Study compared this to commonly used SEM-EDX and inductively coupled plasma mass spectrometry (ICP-MS) approaches for Cd and Ag analyses. Overall, novel use of XRF provided precise analyses of the concentrations of Cd and Ag adsorbed within Na-alginate bead and revealed analyses not determined the concentrations in standard SEM-EDX or previously established in other studies of Na-alginate beads. In addition, this Study shows that XRF may be employed in different fields in biotechnology to analysis the concentrations regarding the elemental adsorption of Na-alginate beads and demonstrate the potential for XRF to monitor the procedures underpinning biotechnology sectors.